Geodetic study of the Afar triple junction - (:unkn) unknown (My University, 2015)
Eastern Africa is a natural laboratory for investigating rifting and break-up. Along the East African Rift, the divergence between Nubia and Somalia plates is accommodated within a mainly tectonic framework dominated by active normal faulting. While Arabia plate moves apart from the African plate couple at the Red Sea and Aden Ridges within a mainly magmatic framework with seafloor spreading. These three plate boundaries meet in Afar Depression forming a triple junction, which correspond to a transition zone between stretched continental lithosphere and oceanic spreading axes, where the role of the mantle plume impacts is determinant. In this thesis, current deformation of the Earth's surface is monitored using geodetics data (GPS, InSAR), in the East African zone where three plates are splitting apart and where the different boundaries encompass areas in all stages of rifting. The current deformation analysis allows clarify extension zone dynamics at short term, taking into account their stage of rifting evolution and especially the variations of magmatic and/or seismic activity. Three studies were carried out at three different spatial scales. The first one considers the whole East African Rift (3000 km), the second one is about the central part of the Afar Depression where the triple junction is situated (a few hundreds of km) and the third focuses on the Asal-Ghoubbet rift in Djibouti (a few tens of km).
Keywords: African Research